Receiver design for the uplink of base station cooperation systems employing SC-FDE modulations - Ribeiro, F. C. (2016)
The presented paper considers the uplink transmission in Base Station (BS) cooperation schemes where Mobile Terminals (MTs) in adjacent cells share the same physical channel. We consider Single-Carrier with Frequency-Domain Equalization (SC-FDE) combined with iterative frequency-domain receivers based on the Iterative Block Decision Feedback Equalization (IB-DFE). We study the quantization requirements when sending the received signals, from different MTs, at different BSs to a central unit that performs the separation of different MTs using iterative frequency-domain receivers. Our performance results show that a relatively coarse quantization, with only 4 bits in the in-phase and quadrature components of the complex envelope already allows close-to-optimum macro-diversity gains, as well as an efficient separation of the transmitted signals associated with each MT.